2020
DOI: 10.3390/s20123565
|View full text |Cite
|
Sign up to set email alerts
|

Simulation System of Electric-Powered Wheelchairs for Training Purposes

Abstract: For some people with severe physical disabilities, the main assistive device to improve their independence and to enhance overall well-being is an electric-powered wheelchair (EPW). However, there is a necessity to offer users EPW training. In this work, the Simcadrom is introduced, which is a virtual reality simulator for EPW driving learning purposes, testing of driving skills and performance, and testing of input interfaces. This simulator uses a joystick as the main input interface, and a virtual reality h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
5
1
2
Order By: Relevance
“…Only the Involvement score is slightly under the average. Compared to literature, our simulator presents great IPQ scores, largely higher than the screen based simulator miWe [32] but still a little lower than scores reported by the two studies using the SimCadRoM simulator [8,9].…”
Section: Sense Of Presencecontrasting
confidence: 58%
See 1 more Smart Citation
“…Only the Involvement score is slightly under the average. Compared to literature, our simulator presents great IPQ scores, largely higher than the screen based simulator miWe [32] but still a little lower than scores reported by the two studies using the SimCadRoM simulator [8,9].…”
Section: Sense Of Presencecontrasting
confidence: 58%
“…Indeed, a study with the screen-based miWe simulator reported a low SoP experienced and associated it with a lack of motion feedback and depth perception [32]. As such, various researches proposed more immersive systems, starting with the use of a VR headset as visual interface to provide depth perception and immersive FOV [8,9] and the addition of other modalities like vibration motion feedback provided by a 6 degree of freedom motion platform [12]. Several researches also compared the use of different simulator configurations like in [14] with the VRSIM-2 simulator where the most immersive configuration allows raters to better evaluate user skills.…”
Section: Related Workmentioning
confidence: 99%
“…However, when considering robotic systems for the rehabilitation area, there is no commercial software or free software that allows one to simulate the behavior of robotic systems oriented to the execution of assistance or rehabilitation tasks. Therefore, the development of new interactive and 3D simulators applied to the area of service robotics is a new trend in the scientific community, whose implementation has been accelerated by the COVID-19 pandemic [ 4 , 43 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em um ambiente virtual, a coleta e medição destas métricas é realizada de forma automatizada, ou seja, à medida que o voluntário completa as tarefas pedidas, o software contabiliza o número de comandos, colisões e o tempo, de forma rápida e em tempo real Hernandez-Ossa et al, 2020). E em ambiente real, não temos esta medição com as mesma precisão e rapidez, pois a métrica "tempo" pode ser quantificada utilizando um cronômetro; a métrica "número de colisões" comumente são contabilizadas a partir de vídeos que são gravados durante a execução das atividades, ou da observação do profissional que está aplicando o treinamento; e o "número de comandos" é contabilizado utilizando micro controladores ou através da observação dos vídeos gravados (Borges, 2016;Caetano et al, 2018).…”
Section: Justificativaunclassified
“…O sistema tem como objetivo quantificar três métricas principais: número de comandos, número de colisões e tempo (Hernandez-Ossa et al, 2020;Younis et al, 2019):…”
Section: Métricasunclassified